2010
DOI: 10.1103/physrevb.81.134424
|View full text |Cite
|
Sign up to set email alerts
|

Spin and orbital moments inFe3O4

Abstract: We report a study of the spin moment in Fe 3 O 4 as a function of temperature using spin-dependent Compton scattering. Magnetic Compton profiles and spin moment values were obtained either side of the Verwey transition for applied magnetic fields of 2.5 and 7 T. The orbital moments, determined by comparison with bulk magnetometry, are almost fully quenched. No evidence of any anomalies in the spin or orbital moments at the Verwey transition was observed. The magnetic Compton profiles have the characteristic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It is not surprising that the natural non-milled magnetite has the largest saturation magnetization, 91 A m 2 /kg. This is almost the theoretical value, the spin moment in the inverse spinel structure magnetite, determined as ≈ 4 Bohr magnetons (92 A m 2 /kg) [16], indicating high purity and defect-free structure of the mineral. The saturation magnetization decreases with milling to 69.2 A m 2 /kg.…”
Section: Resultssupporting
confidence: 56%
“…It is not surprising that the natural non-milled magnetite has the largest saturation magnetization, 91 A m 2 /kg. This is almost the theoretical value, the spin moment in the inverse spinel structure magnetite, determined as ≈ 4 Bohr magnetons (92 A m 2 /kg) [16], indicating high purity and defect-free structure of the mineral. The saturation magnetization decreases with milling to 69.2 A m 2 /kg.…”
Section: Resultssupporting
confidence: 56%
“…By the use of X-ray magnetic circular dichroism (XMCD) sum rules [13] and also by Compton scattering [14], such an orbital moment has indeed been observed. On the other hand, more recent results, again utilizing XMCD [5,15,16] and Compton scattering [17], only found a clear vanishing orbital moment. It has been shown that the integration range for sum-rule analysis also plays an important role [5,16].…”
mentioning
confidence: 95%
“…Magnetic Compton scattering [18] measures the projec-tion of the spin-resolved momentum density. Here components arising from spin-paired electrons cancel, allowing the spin magnetic moment [5], and spin polarisation to be determined [19]. Compton profiles (CPs), J(p z ), and magnetic Compton profiles (MCPs), J mag (p z ) are defined as…”
Section: Introductionmentioning
confidence: 99%